Budaya dan Pembangunan Ekonomi: Sebuah Kajian terhadap Artikel Chavoshbashi dan Kawan-Kawan - Asmin, Ferdinal (Jurnal Studi Komunikasi, 2018)
The research of the cultural effect on economic development is always interesting for many researchers. An article of Chavoshbashi et al. has provided an understanding to study the cultural effect by using a dynamics system approach. This paper reviewed the article by focusing on their system thinking. This review strengthened an argument that it is important to consider the cultural values in the economic development.